Retirement saving of the self-employed - Rowena Crawford; Heidi Karjalainen (Institute for Fiscal Studies (IFS), 2020)
The proportion of self-employed workers contributing to a private pension has been steadily declining since the 1990s. This is in contrast to private-sector employees, for whom the rate of pension participation has dramatically increased as a result of automatic enrolment. Furthermore, even before the introduction of automatic enrolment, the rate of decline in pension participation was faster among the self-employed than private-sector employees. In this report, we seek to explain this decline in pension saving amongst the self-employed. We examine the extent to which the decline has been driven by the changing characteristics of the self-employed population. We then explore changing attitudes towards pension saving, and changes in other forms of saving that might represent alternative ways of saving for retirement (and therefore provide an explanation for the patterns in pension saving).
Keywords: 330; Selbstständige; Rentenfinanzierung